Long-term game engagement, well-being, and firm value among Gen Z university students - Danial Muhammad Wirdyansyah; Muhammad Ridho Wasturedana (Universitas Pendidikan Nasional, 2026)
The digital gaming industry in Indonesia has experienced rapid user growth, yet this expansion has not been consistently accompanied by proportional revenue performance, highlighting the importance of understanding sustainable user engagement. This study investigates the determinants of Sustainable Usage Intention (SUI) and its role in shaping Player Well-Being (PWB) and Firm Value Perception (FVP) within the context of mobile gaming. Drawing on the Technology Acceptance Model (TAM) and Hedonic Information Systems perspective, this research examines the effects of perceived enjoyment, perceived ease of use, and perceived usefulness on SUI, PWB, and FVP. Data were collected from 170 Indonesian Gen Z university students using a cross-sectional survey and analyzed with PLS-SEM. The results demonstrate that perceived usefulness and perceived enjoyment significantly influence SUI, while SUI plays a pivotal mediating role in strengthening both player well-being and firm value perception. The findings contribute to post-adoption literature by emphasizing sustainable engagement rather than mere adoption and offer practical implications for game developers seeking to balance user well-being with long-term value creation in emerging markets.